DC transformer modeling and control of DC-DC buck converter - Sarun Soman; Nishtha Shelly; Ciji Pearl Kurian; Sudheer Kumar TS (Institute of Advanced Engineering and Science, 2019)
Switching Power Converters convert one form of power to another with high ef-ciency and accurate control.One of the most widely used DC-DC Converter is Buck Converter. Control is invariably required to maintain the output voltage/current in spite of variations in source/load. In order to design the controller and gain insight about the system a dynamic model needs to be developed. Modeling techniques widely used are state space averaging and PWM switch model. In this paper DC transformer modeling technique is used to develop the averaged model of the converter. One of the advantages of this model is that it can be implemented in Spice simulator using basic circuit elements. The same model can be used for time domain as well as frequency domain analysis. Analog type-II compensator is designed to compensate the system. Simulation and experimental results for start-up transient and load transient are shown to validate the model.